Modified Bogolyubov’s Derivation of the Two-fluid Hydrodynamics - Shygorin, P.; Svidzynskyj, A. (Відділення фізики і астрономії НАН України, 2010)
A consistent microscopic derivation of the two-fluid hydrodynamics for superfluid helium-4 in the ideal approximation is represented The starting point in our formalism is a system of Heisenberg’s equation of motion for both normal and anomalous correlation functions. The use of a mixed Wigner representation allows us to perform the expansion of the equations of motion for correlation functions in gradients directly, very easily, and with a rigorous mathematics. To find the hydrodynamic flows, we have constructed a local equilibrium statistical operator for superfluid helium in the reference frame, where the condensate is at rest. У роботi представлено послiдовний мiкроскопiчний вивiд дворiдинної гiдродинамiки надплинного гелiю-4 в iдеальному наближеннi. Вiдправною точкою у нашому формалiзмi є система гайзенбергiвських рiвнянь руху для нормальної та аномальної кореляцiйних функцiй. Використання мiшаного представлення Вiгнера дозволяє легко i з математичною строгiстю виконати розклад рiвнянь руху для кореляцiйних функцiй за градiєнтами. Для обчислення гiдродинамiчних потокiв у роботi побудовано локально-рiвноважний статистичний оператор надплинної рiдини в системi вiдлiку, пов’язанiй з конденсатом.